Effect of integrated nutrient management on roselle ( Hibiscus sabdariffa) productivity, its mineral nutrition and soil properties - Saha, A R; Maitra, D N; Majumdar, B; Saha, S; Mitra, S (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was undertaken during 2003-04 to study the effect of combined application of inorganic fertilizers, organic manure and biofertilizer on the productivity, mineral nutrition of roselle (Hibiscus sabdariffa L.) and on soil properties. Seventy-five per cent NPK applied through chemical fertilizer in conjunction with organic manures (poultry manure or farmyard manure) and biofertilizer (Azotobacter) improved roselle fibre yield by 3-13% over 100% NPK through chemical fertilizer. Highest N, P and K uptake was recorded in 75% NPK + poultry manure + Azotobacter treatment, followed by 75% NPK + farmyard manure + Azotobacter. Post - harvest soil analysis showed that soil fertility status was enriched in respect of organic carbon, available N, P and K where inorganic fertilizer was incorporated in association with organic manures and biofertilizer. Integrated use of 75% NPK + poultry manure + Azotobacter was found optimum for roselle fibre production and maintenance of soil fertility under Typic Ustochrept.